Toxic effects on astrocytes of extracellular vesicles from CSF of multiple sclerosis patients: a pilot in vitro study - Ragonese, Paolo; Liegro, Italia; Schiera, Gabriella; Salemi, Giuseppe; Realmuto, Sabrina; Liegro, Carlo; Proia, Patrizia (Polish Journal of Pathology, 2020)
Multiple sclerosis (MS) is an autoimmune and degenerative disorder of the central nervous system (CNS) that causes a progressive loss of motor and cognitive performances. Moreover, since the earlier phases, axonal loss as well as neuronal degeneration and a failure of oligodendrocytes to promote myelin repair have been demonstrated. In previous studies, it has been shown that the treatment of rat neuronal primary cultures with serum from MS patients can be toxic for neurons. Here we report a pilot investigation showing that CSF from patients contains extracellular vesicles (EVs) able to induce cell death in rat cultured astrocytes. Although these data are still preliminary, they suggest at least two notable considerations: i) EVs can be instrumental to pathology, and their concentration in CSF might be proportional to MS severity; ii) astrocytes can be part of the degenerative process. As a consequence, we propose that cultured astrocytes can be used as a model to study the toxicity of EVs from patients affected by MS at different stages. In addition, we suggest that EVs and their cargoes might be used as biomarkers of MS severity.